Differential expression and molecular genetic characteristics of CD36 antigen in platelet donor database in Shaanxi province, China - WANG Tianju; QI Jun; WANG Manni; LI Yuhui; SHANG Lixia; CHEN Le; WANG Xiaofang (Zhongguo shuxue zazhi)
[Objective] To screen the frequency of CD36 antigen expression in platelet donor database in Shaanxi province and analyze the molecular genetic characteristics of samples with CD36 antigen deficiency and low expression. [Methods] A total of 525 platelet donors samples were randomly collected during May 2023. CD36-FITC monoclonal antibody was used for immunofluorescence labeling, and flow cytometry was applied to detect the expression of CD36 antigen on platelets. For samples with CD36 antigen deficiency on platelets, the expression of CD36 on monocytes was further detected. Samples with CD36 antigen deficiency and low expression were sequenced and analyzed. [Results] Among the 525 blood samples, 99.24% (521/525) showed positive expression of CD36 antigen. There were differences in the expression intensity of CD36 antigen, with low expression accounting for 3.43% (18/525) and CD36 antigen deficiency accounting for 0.76% (4/525), all of which were type Ⅱ deficiency. The exon mutation frequency of CD36 type Ⅱ deficiency and low expression samples was 31.82% (7/22), and the exon mutation types were 121-1_126delGCAAGTT, 329-330delAC, 1142T>G, 1204-1246dupl 43bp, 1221G>A, and 1228-1239delATTGTGCCTATT. All four cases of CD36 type Ⅱ deficiency had a 121-6 T>C mutation in intron 3. All CD36 low expression samples had a mutation of 282-10A>G, and 121-6T>C mutation rate was 61.1%(11/18). [Conclusion] There were differences in the expression of CD36 antigen in the platelet donor database in Shaanxi province, which may be caused by multiple molecular genetic variations. The frequency of CD36 antigen deficiency in Shaanxi was lower than that of Han, Zhuang and Yao populations in southern China. This study provides references for solving the CD36 antibody mediated transfusion reaction and auxiliary treatment of diseases caused by CD36 antigen deficiency in the future. It also provides a basis for investigating the molecular mechanisms of CD36 deficiency and low expression.